Using aluminothermic reduction of nickel oxide in formation of AlNi intermetallic compound. Issue 4 (2nd October 2018) - Jajarmi, E.; Soltanieh, M.; Nasiri, H.
ABSTRACT: The reduction of nickel oxide and the formation of AlNi intermetalic phase at 1200°C for 2.5 till 10 min interval, during the aluminothermic method were studied, simultaneously. Aluminium was used as a reduction agent of nickel oxide in molten cryolite (Na3 AlF6 ). The changes in the amount of Ni in primitive metal samples were determined by atomic absorption analysis at different times. The achieved microstructure in quenched samples was observed by SEM. The prepared phases were recognised by XRD and EDS analysis. The results revealed that samples were combination of AlNi, Al3 Ni2, Al3 Ni and Al in the absence of Ni, NiO and Al2 O3 phases. The increasing of time causes the higher amount of AlNi phase to a continuous network.